2017
DOI: 10.18282/amor.v3.is1.197
|View full text |Cite
|
Sign up to set email alerts
|

The role of neoadjuvant chemotherapy in the surgical management of women with breast cancer in a middle-income country

Abstract: Neoadjuvant chemotherapy (NAC) in women with large breast tumours can downsize tumours to allow for breast conservation surgery (BCs). The aim of this study is to compare the BCs rate between those who had NAC versus those who underwent surgery first and to determine the factors affecting response rate. 1,183 patients, who had surgery for breast cancer in a single institution from December 2012 to December 2015, were included in this study. 80 (6.8%) patients had NAC. Patient and tumours characteristics, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Yip et al reported the outcome of breast cancer patients who presented with very large tumour and who were treated with neoadjuvant chemotherapy at a single centre in Malaysia. These patients achieved similar breast conservation rate as those presented with early stage disease [8] . 40%-50% of breast cancer patients presented as stage 3 or 4 disease at many parts of developing world; therefore, apart from assessing the clinical and pathological predictors of response to treatment, the health systems performance as a whole should also be assessed in order to achieve better outcome.…”
mentioning
confidence: 61%
“…Yip et al reported the outcome of breast cancer patients who presented with very large tumour and who were treated with neoadjuvant chemotherapy at a single centre in Malaysia. These patients achieved similar breast conservation rate as those presented with early stage disease [8] . 40%-50% of breast cancer patients presented as stage 3 or 4 disease at many parts of developing world; therefore, apart from assessing the clinical and pathological predictors of response to treatment, the health systems performance as a whole should also be assessed in order to achieve better outcome.…”
mentioning
confidence: 61%